Lack of Platelet Response to Collagen Associated with an Autoantibody against Glycoprotein Ia: A Novel Cause of Acquired Qualitative Platelet Dysfunction - Deckmyn, Hans; Chew, Shern L; Vermylen, Jos (Thrombosis and Haemostasis, 1990)
Platelets from a patient with an acquired hemorrhagic disorder had a severely impaired response to collagen, whereas platelet aggregation to other agonists and coagulations tests were normal. No abnormalities of the patient’s platelet membrane glycoproteins (GP) were seen.Tleatment of the patient with immunosuppressive agents temporarily improved both the bleeding tendency and the collagen responsiveness of the platelets. An IgG was found to be present in the plasma, directed against a protein comigrating with GPIa, and coadsorbing with GPIa to insoluble collagen fibers in a Mg+2-dependent manner. Furtherrnore, GPIa was recognized by the patient’s antibody when affinity-purified GPIa-IIa was used as antigen. Finally, the GPIa-IIa complex was immunoprecipitated from a platelet lysate by patient’s plasma.In addition, purified platelet specific IgG’s from the patient inhibited aggregation of normal platelets induced by collagen or by wheat germ agglutinin. We conclude that the lack of response to collagen of the patient’s platelets may well be due to the presence of an autoantibody against GPIa.